Everlasting impact of initial perturbations on first-passage times of non-Markovian random walks - N. Levernier; T. V. Mendes; O. Bénichou; R. Voituriez; T. Guérin (Nature Communications, 2022)
The persistence of random walker can quantify the kinetics of transport limited reactions and predict the time to reach a target, but is challenging for non-stationary random processes with a large number of degrees of freedom. The authors introduce a method to determine the persistence exponent of random processes with general non-stationary dynamics.